Effectiveness of the 2000–2006 National Road Traffic Safety Programme Implementation in Latvia - Aldis Lama; Juris Smirnovs; Juris Naudžuns (The Baltic Journal of Road and Bridge Engineering)
Road traffic safety programme is one the most important national level documents setting the main goals in road traffic safety work. The First National Road Traffic Safety Programme in Latvia was adopted by the Cabinet of Ministers in 2000. The following article analyses results of the programme implementation within period 2000–2005 and gives a detailed look on the most effective measures under Latvian circumstances. Cost-benefit ratio of the Programme implementation is good – 1,7. However, it has to be mentioned that financing the Programme was carried out only by 63 % and defined goals are only partly achieved.